Reading the barrier landscape of Al/(CdO:ZnO:NiO:Ti)/p-type Si Schottky diodes through temperature-swept current-voltage data - Tascioglu, I.; Yeriskin, S. Altindal; Arda, L.; Yildiz, K.; Dere, A.; Yakuphanoglu, F. (Elsevier Science Sa, 2026)
Multi-oxide-interlayered aluminum/p-type silicon Schottky diodes (SDs) were fabricated and examined using temperature-swept current-voltage (I-V) measurements. The quaternary CdO:ZnO:NiO:Ti film was obtained by a sol-gel route, deposited by spin coating, thermally treated, and finalized with aluminum rectifying contacts formed by vacuum evaporation. The device exhibits a pronounced thermal response and clear deviations from ideal thermionic-emission behavior, as evidenced by method-and bias-sensitive diode parameters. To interpret these non-idealities, barrier non-uniformity was analyzed within a Gaussian-based framework and supported by modified Richardson evaluation, which jointly indicates the presence of two temperature regions associated with different effective barrier statistics. In parallel, electrically active defects at the junction were assessed by extracting the energy-dependent defect density from forward-bias characteristics using the Card-Rhoderick formalism, providing complementary insight into the interfacial contribution to forward conduction. The combined analysis provides a consistent physical picture that links the observed I-V curvature to barrier-landscape effects and junction-defect activity. It demonstrates that the multi-oxide interlayer constitutes a practical platform for temperature-dependent SD diagnostics and performance assessment.
Keywords: Non-Uniformity Parameters; Temperature Sensitivity; Barrier Inhomogeneity; Double Gaussian Distribution; Modified Richardson Analysis; Cdo:Zno:Nio:Ti Film